Arabidopsis CCoAOMT1 Plays a Role in Drought Stress Response via ROS- and ABA-Dependent Manners - Hyun Jin Chun; Lack Hyeon Lim; Mi Sun Cheong; Dongwon Baek; Mi Suk Park; Hyun Min Cho; Su Hyeon Lee; Byung Jun Jin; Dong Hyeon No; Ye Jin Cha; Yong Bok Lee; Jong Chan Hong; et al. (Plants, 2021)
Plants possess adaptive reprogramed modules to prolonged environmental stresses, including adjustment of metabolism and gene expression for physiological and morphological adaptation. CCoAOMT1 encodes a caffeoyl CoA O-methyltransferase and is known to play an important role in adaptation of Arabidopsis plants to prolonged saline stress. In this study, we showed that the CCoAOMT1 gene plays a role in drought stress response. Transcript of CCoAOMT1 was induced by salt, dehydration (drought), and methyl viologen (MV), and loss of function mutants of CCoAOMT1, ccoaomt1-1, and ccoaomt1-2 exhibit hypersensitive phenotypes to drought and MV stresses. The ccoaomt1 mutants accumulated higher level of H2O2 in the leaves and expressed lower levels of drought-responsive genes including RD29B, RD20, RD29A, and ERD1, as well as ABA3 3 and NCED3 encoding ABA biosynthesis enzymes during drought stress compared to wild-type plants. A seed germination assay of ccoaomt1 mutants in the presence of ABA also revealed that CCoAOMT1 functions in ABA response. Our data suggests that CCoAOMT1 plays a positive role in response to drought stress response by regulating H2O2 accumulation and ABA signaling.